Hambatan Partisipasi Skrining Kanker Serviks pada Perempuan di Kelurahan Pabuara, Jawa Barat: Studi Kuantitatif - Nurlelasari Harahap; Halimatun Syakdiyah Harahap (Jurnal Sehat Mandiri, 2026)
Cervical cancer remains a major public health problem among women in Indonesia, while participation in cervical cancer screening programs remains low despite the availability of screening services. Low screening uptake is influenced by various barriers related to psychological, informational, and healthcare access factors. This study aimed to identify barriers affecting women’s participation in cervical cancer screening in Pabuaran Village, West Java. A quantitative study with a cross-sectional design was conducted among 113 women aged 18 years and older selected through convenience sampling. Data were collected using the Cervical Cancer Awareness Measure (Cervical CAM) questionnaire and analyzed using descriptive statistics with SPSS. The findings revealed that the most common barriers were fear of the Pap smear procedure (44.2%), lack of information about cervical cancer screening (13.3%), and unspecified personal or cultural reasons (14.2%). In contrast, logistical barriers such as distance to healthcare facilities and long waiting times were reported less frequently. The study concludes that psychological barriers and limited information are the primary factors contributing to low participation in cervical cancer screening. Therefore, targeted health education, culturally sensitive counseling, and community-based interventions are needed to improve women’s awareness and increase cervical cancer screening coverage.